Sistem Informasi Arsip Data Kepegawaian Menggunakan Metode Agile Development Dinas Kesejahteraan Sosial - Maria Claudia Letsoin (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The personnel data archive information system plays an important role in storing the existing data in the Department of Social Welfare. However, in this case, the Department of Social Welfare still performs personnel data archiving manually, which certainly causes complications in searching for employee data and updating employee information, as well as the lack of adequate security systems, thus increasing the risk of data leaks or unauthorized access. Therefore, a personnel data archive information system was developed, which is one of the best options for improving the performance of the Department of Social Welfare.This personnel data archive information system is built based on an Android application, which is a technological solution designed to assist in managing data archiving. This system utilizes the Android platform as a user interface, allowing users to access personnel data archiving anytime and anywhere through mobile devices. This Android-based application aims to provide facilities such as fast personnel data search and easier data updates compared to the previous manual system.